Oil Development and Intimate Partner Violence: Implementation of Section 8 Housing Policies in the Bakken Region of North Dakota and Montana. Issue 21 (November 2018) - Jayasundara, Dheeshana S.; Legerski, Elizabeth M.; Danis, Fran S.; Ruddell, Rick
One of the challenges survivors of intimate partner violence (IPV) often face is securing safe and affordable housing. Many survivors qualify for public housing programs such as the Section 8 Project-Based Rental Assistance (PBRA) program and tenant-based Housing Choice Voucher Program (HCVP). These programs can be vital for survivors fleeing abuse and trying to rebuild their lives. But how might regional conditions such as rapid population growth resulting from an oil boom affect the implementation of such programs for survivors? In addition, what role might such policies play in preventing future violence in resource boom communities? Analyzing existing policies and qualitative data collected from in-depth interviews with survivors, community members, and service providers in the Bakken region of North Dakota and Montana, we evaluate the implementation of Section 8 housing programs in oil-affected communities for survivors of IPV. We find that survivors of IPV often had a difficult time accessing affordable housing in the Bakken. Eligibility restrictions prevented some survivors from utilizing Section 8 housing programs, some landlords opted out of Section 8 program participation at the height of the oil boom, and the housing crisis may have simultaneously contributed to low utilization of housing vouchers. These conditions increased vulnerability for IPV survivors. We conclude by exploring the impact of the Violence Against Women Act (VAWA), state, and local initiatives on housing access and affordability, and the efficacy of Section 8 housing programs during the oil boom. Understanding the relationship between natural resource development, rapid population increases, housing inflation, and Section 8 housing programs should be considered as policy makers prioritize social programs in boomtown communities that may affect the well-being and safety of IPV survivors.